Investigating Primary Spray Structures of Diesel Sprays with an Optimized Light Sheet Fluorescence Imaging Approach and X-Ray Phase Contrast Imaging - Durst, Alexander; Wang, Jing; Wensing, Michael (19th International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2018)
In this article, we show an optimized setup for investigating primary spray structures of Diesel sprays with light sheet fluorescence microscopic imaging in the visible range of the spectrum. As demonstrated by us in [1], the use of Nile Red as tracer dye enables the use of a non-intensified camera as proposed by Berrocal [2] for alkane based surrogate fuels and real world fuels for the first time. Comparative measurements of the fluorescence of Eosin Y and Nile Red dissolved in Calibration Fluid, Diesel and Gasoline prove the suitability for all three fuels. The optimized setup enables a thinner light sheet with higher laser intensities and hence clearer and more detailed images of the primary breakup. Moreover, for the same operating conditions x-ray phase contrast imaging (PCI) was carried out at the Advanced Photon Source (APS) of the Argonne National Laboratory (ANL). With both techniques, the transient opening process of the injector as well as the stationary phase of the spray are investigated. Both techniques give a very plastic impression of the initial spray formation as well as during the stationary phase. The measurements reveal the existence of a small area after the nozzle exit where an intact liquid jet exists. In the further progress, the spray disintegrates into ligaments from the surface but the spray stays narrow and majority of the fuel mass concentrated at the spray axi
Keywords: LIF; Diesel; Primary Breakup; Atomization; X-Ray Phase Contrast